Dietary factors in patients with Parkinson's disease: An integrative review (Research, Society and Development, 2025)
Introduction: Parkinson's disease (PD) is a neurodegenerative condition that affects millions of people globally and is characterized by motor and non-motor symptoms. Diet has been shown to be a relevant modifiable risk factor in the development and progression of PD. Studies suggest that certain dietary patterns may influence the pathophysiology of PD, impacting neuroinflammation, oxidative stress, and the gut microbiome. Objective: To analyze the most recent scientific evidence on the impact of diet on various aspects of PD, including risk, progression, symptom management, and quality of life. Methodology: Integrative literature review on the impact of diet on various aspects of PD. Integrative literature review conducted with PubMed database, between 2019 and 2025, using the descriptors "Parkinson's disease", "Diet", and "Nutrition", associated by the Boolean operator "AND". Seven articles were selected for analysis. Results and Discussion: The review found that diets rich in fruits, vegetables, whole grains, and fish are consistently associated with a lower risk of PD. Western dietary patterns, rich in processed foods and red meat, increase the risk. Evidence suggests that antioxidants and vitamins may exert neuroprotective effects. The gut microbiome also plays an important role, with high-fiber diets showing beneficial effects. Specialized diets, such as the ketogenic diet, have shown improvements in motor and non-motor symptoms, although long-term safety requires further study. Conclusion: Good-quality nutrition is associated with lower risks and better management of PD symptoms. Personalized dietary interventions emerge as a promising avenue for the treatment of PD, but further studies are needed to validate these approaches.